TRANSFORMING AGRICULTURE: THE ROLE OF HYDROGEL IN CULTIVATING A GREENER AND MORE SUSTAINABLE FUTURE - Bidyut Kumar Murmu; Simran Budhathoki; Rhea Vinod Nair; Veena Krishna Das; Krupa S (The Bioscan, 2025)
Hydrogels have become a revolutionary innovation in farming, tackling major issues like lack of water, declining soil health, and wasteful use of fertilizers. These incredibly absorbent materials can hold up to 400 to 1500 times their weight in water, greatly increasing soil water levels and cutting down on the need for watering, particularly in arid regions. They enhance the soil structure, enabling it to retain water and support plant growth more effectively. Hydrogels not only aid in water retention but also improve nutrient delivery to plants, making them highly efficient tools for modern agriculture. This review explores the latest advancements in hydrogel applications for sustainable agriculture and their role in reducing environmental impact, enhancing productivity, and addressing climate-resilient farming.